2017
DOI: 10.1055/s-0043-118342
|View full text |Cite
|
Sign up to set email alerts
|

Time Course Change in Muscle Swelling: High-Intensity vs. Blood Flow Restriction Exercise

Abstract: This study determined the time course for changes in muscle swelling and plasma volume following high (HI) and low-intensity resistance exercise with blood-flow restriction (LI-BFR). Ten male participants (22.1±3.0 yrs) completed three experimental conditions: high-intensity exercise (HI - 80% of 1RM), low-intensity exercise with BFR (LI-BFR -20% of 1RM, and 160 mmHg of BFR), and control (CON - no exercise or BFR). Muscle cross-sectional area (mCSA), muscle thickness, thigh circumference, and percentage change… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(36 citation statements)
references
References 47 publications
4
32
0
Order By: Relevance
“…Hence, our results also suggest that releasing the pressure of the cuffs during the rest periods between sets does not attenuate the exercise-induced muscle swelling response. These outcomes corroborate previous findings from our research group that also demonstrated similar levels of muscle swelling with both low-load resistance exercise with BFR and conventional high-load resistance exercise (Freitas et al, 2017). Yasuda et al (2015) also observed similar changes in muscle thickness following four sets of low-load (20% of 1-RM) resistance exercise with and without BFR performed to failure.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Hence, our results also suggest that releasing the pressure of the cuffs during the rest periods between sets does not attenuate the exercise-induced muscle swelling response. These outcomes corroborate previous findings from our research group that also demonstrated similar levels of muscle swelling with both low-load resistance exercise with BFR and conventional high-load resistance exercise (Freitas et al, 2017). Yasuda et al (2015) also observed similar changes in muscle thickness following four sets of low-load (20% of 1-RM) resistance exercise with and without BFR performed to failure.…”
Section: Discussionsupporting
confidence: 90%
“…Following sterilization, the participants' index or middle finger was pricked, and a small blood sample was collected into a heparinized plastic microhematocrit tube, which was centrifuged to separate Hct from plasma. Hct-to-plasma percentage was determined in each sample using a micro-capillary reader (Damon/IEC Division, Needham, MA).% PV were calculated using the equation below (Van Beaumont, 1972), previously used by our research group (Freitas et al, 2017):…”
Section: Hematocrit Levels and Plasma Volume Changesmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the abovementioned issues may indicate that seated KEE induced a greater mechanical and physiologic stress in VL than supine KEE, but these responses are similar in RF between both exercises. Therefore, as previously mentioned, metabolic, mechanical, and physiologic responses to exercise are purportedly related to muscle swelling, which may partially explain the findings of the current study [5,27,28].…”
Section: Discussionsupporting
confidence: 71%
“…In addition, consistent with our hypothesis, the seated KEE produced greater peak torque and work output than supine KEE. Acute muscle swelling (i.e., immediately after exercise) is an indication of localized fluid from reactive hyperemia and is related to a metabolic/mechanical/physiological muscle response to exercise [5,27,28]. Thus, it is important to note that MT is an indirect measure of muscle swelling [5,22], and the data of the current study showed good intersession reliability [29].…”
Section: Discussionmentioning
confidence: 58%